Relatório de viagem ao exterior: [Nigéria] - SOUZA, Kaiser Gonçalves de (2009)
Seminário "Exploration and Exploitation of Deep Mineral Resources in the Area: challenges for Africa and opportunities for collaborative research in the South Atlantic ocean"